Model Edukasi Pajak UMKM: Studi Kasus Liquid Fotocopy Kota Bengkulu - Putra, Danang Adi; Indriani, Rini; Midiastuty, Pratana Puspa; Suranta, Eddy; Rahmat, Agus (Penerbit Goodwood, 2025)
Purpose: This study aims to provide training and guidance to Small and Medium Enterprises (MSMEs) on accounting practices, tax calculation, and tax reporting to foster business growth and ensure compliance. Methodology/approach: This study focuses on Liquid Fotocopy, a small business in Bengkulu that provides office supplies and photocopy services. The training included lectures, practical exercises, and Q&A sessions to address challenges in accounting and tax reporting, along with hands-on guidance on bookkeeping and tax calculations. Results/findings: The training enhanced the participants' understanding of accounting practices, allowing them to separate personal and business finances, track revenues and expenses, and calculate taxes accurately. This helps businesses gain insights into their financial performance and make informed decisions. Conclusions: The program effectively addressed gaps in accounting and tax-reporting practices for liquid photocopying. With the acquired knowledge, the business is now better positioned to manage its finances and fulfill its tax obligations. Limitations: This study was limited to a single SME, and the findings may not apply universally to businesses in different sectors or regions. Contribution: This study enhances financial literacy and tax compliance in MSMEs. It provides practical solutions for MSMEs to improve financial management and supports policy efforts to strengthen Indonesia's financial sector.